Research on Mathematical Model and Flank Deviation Correction of Spiral Bevel Gear by Duplex Helical Method - Longlong Geng; Jing Deng; Shaowu Nie; Xiaozhong Deng; Chuang Jiang; Zhengyang Han (Jixie chuandong)
A mathematical model is established to machine spiral bevel gears by duplex helical method. Based on the meshing principle of the gear， the digital representation of the spiral bevel gear tooth surface processed by the double helix method and the construction of discrete tooth surface points are completed， and the influence degree of each machine parameter error on tooth surface topology structure are analyzed. The correction model of tooth surface is built， through numerical example verification， the results show that tooth surface deviation is reduced effectively.